Analisis Faktor Risiko Kecemasan Ibu Hamil Trimester III Menjelang Persalinan di RSUD Dr. Adhyatma, MPH Provinsi Jawa Tengah - Salsa Putri Kusumah; Sri Rejeki; Muhammad Riza Setiawan (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Referring to the World Health Organization (WHO) in 2020, around 8-10% of pregnant women experience anxiety during pregnancy, which then increases to around 12% when approaching childbirth. Anxiety conditions in third trimester pregnant women can produce psychological changes compared to the previous trimester, because at this stage the pregnancy condition is getting bigger. The impact is that the anxiety tends to continue to be felt until the delivery period. The purpose of this study was to determine the relationship between risk factors for anxiety in third trimester pregnant women before delivery at Dr. Adhyatma Hospital, MPH, Central Java Province in 2024. This study used an observational analytic design with a cross sectional approach. The sample in the study were third trimester pregnant women who visited obgyn clinic at RSUD Dr. Adhyatma, MPH Central Java Province in 2024. Sampling technique with total sampling method based on inclusion criteria. The research time was in January 2024. Data were processed with Fisher's Exact test using Statistical Package for The Social Sciences (SPSS) application. The results of the study showed that the p value at high risk was related to maternal age (p=0.860), gravida status (p=0.420), education (p=0.660), employment (p=0.640), economic status (p=0.280), ANC history (p=0.700), marital status (p=0.880), medical conditions (p=0.880), environment (p=0.860), health facilities (p=0.820), transportation support (p=0.880), family support (p=0.580 ) and husband's support (p=0.400), which means there is no significant relationship with anxiety of pregnant women in the third trimester at RSUD Dr. Adhyatma, MPH Central Java Province in 2024.